PERSPEKTIF SUMBER PENDANAAN SEBAGAI STRATEGI POLITISASI PEMERINTAH DALAM PENINGKATAN STRUKTUR BELANJA MODAL DAERAH - Husin, Dasmi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This study aims to look at the role of government (political strategy of the budget) inallocating capital expenditure structure by testing the General Allocation Fund (DAU)and revenue (PAD) which dioreintasikan on building / structure Capex (BM) area.This study uses a combination of research methods (mixed method) that combinesquantitative and qualitative research methods. The data were processed usingSPSS. The results showed that the variables simultaneously DAU and PAD do notaffect capital expenditure, but only partially PAD variables that affect predictions oflocal government capital expenditures. The proportion and fund management ishighly dependent on government policy. The funding source is not necessarily a lotlarger nominal allocated to optimize capital expenditure. The function of governmentas an agent can not be separated from the function of the politicization of theparliament. Both as a public agency because of head and MPs both selected andtrusted by the people. Political function of legislative - executive and administrativefunctions at the same executive role in determining the allocation of resources andthe use of capital expenditure penanaan area.Keywords: Proportion of capital expenditure structure